Techniques In Dowel Pin Manufacturing With S45c Material For Quality Control - Abdul Rahman Agung Ramadhan; Sandy Suryady (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
The cylinder block is a housing of cylindrical tubes in which there is a cooling water channel. In these channels there is also the camshaft housing and the bearing seat tube, which is equipped with holes with various threads for attaching other parts that have to do with the cylinder block. One of the components to bind or connect the cylinder block is the Dowel Pin. The function of the Dowel Pin is to lock and close the connection between the engine block, cylinder block and head. Making Dowel Pins using S45C carbon steel material. S45C carbon steel is a medium steel with a carbon content of 0.48% already in rolled form. The process of making Dowel Pins includes, The cutting process is cutting from the initial length of 12 meters to 109 mm. The turning process is a machining process for the workpiece feeding process where the incision is made by rotating the workpiece, in this process a level lathe is carried out with a length of 109 mm and a width of 16 mm, 14 mm, 11 mm, and 7 mm. Drilling process where this process expands / enlarges the plate hole which can be done with a drill rod with a hole diameter of 4 mm. The grinding process is part of the finishing process used to remove parts of the workpiece that are uneven. And finally, Quality Control is done to check whether or not an item is produced.